From Electoral politics to Sustainable politics: Challenges and Prospects for Civil Society in Pakistan (Al-Qamar, 2022)
Electoral politics has long been a dominant feature of Pakistan's political landscape, with political parties vying for power through democratic means. However, this approach has often led to short-term thinking and a lack of focus on sustainable development. This paper explores the challenges and prospects of transitioning from electoral politics to sustainable politics in Pakistan. It examines the current political, economic, and social context of the country, including the role of the military, corruption, and climate change, and analyzes the potential for a shift towards sustainable policies that prioritize long-term planning and environmental protection. The paper concludes by highlighting the opportunities for a more sustainable future for Pakistan and the role of political leadership in achieving this goal. Unfortunately, in a social contract between state and people of Pakistan, state has dishonored its obligation many times. The role of one of the states institution had remained over developed and to remove the label of garrison state to a welfare state, a great deal of responsibility lies with politicians and their electoral politics.
Keywords: Electoral politics; Political leadership; State’s Institutions; civil society; democracy